Leveraging implementation science theories to develop and expand the use of a penicillin allergy de-labeling intervention - Esra Alagoz; Megan Saucke; Prakash Balasubramanian; Tyler Liebenstein; Sujani Kakumanu (BMC, 2024)
Abstract Background Penicillin allergy is the most frequently reported drug allergy, yet most patients can tolerate the drug if challenged. Despite this discrepancy, large scale penicillin allergy de-labeling interventions have not been widely implemented in many health care systems. The application of a multi-method implementation science approach can provide key tools to study this evidence to practice gap and provide insight to successfully operationalize penicillin allergy evaluation in real-world clinical settings. Methods We followed a four-step process that leverages qualitative analysis to design evidence-based, actionable strategies to develop an intervention. First, we specified the clinician-perceived barriers to penicillin allergy de-labeling (intervention targets). We then mapped intervention targets onto Theoretical Domains Framework (domains and constructs) and found the root causes of behavior. Next, we linked root causes of behavior with intervention functions (BCW). In the final step, we synthesized participants' suggestions for process improvement with implementation strategies aligning with the intervention functions. Results Evidence-based strategies such as focused education and training in penicillin allergy evaluation can address knowledge and confidence barriers reported by frontline clinicians. Other key strategies involve developing a system of champions, improving communications systems, and restructuring the healthcare team. Implementation mapping can provide a powerful multi-method framework to study, design, and customize intervention strategies. Conclusion: Empowering clinicians beyond allergy specialists to conduct penicillin allergy assessments requires designing new workflows and systems and providing additional knowledge to those clinicians.